Adaptive Response of the Holdase Chaperone Network of Acidithiobacillus Ferrooxidans Atcc 23270 to Stresses and Energy Sources - Levican-Jaque, G; Tello-Reyes, M; Muñoz-Villagran, C; Izquierdo-Fiallo, K (Springer Science and Business Media B.V., 2025)
Acidithiobacillus ferrooxidans is a chemolithoautotrophic acidophilic bacterium belonging to microbial communities involved in sulfide ore bioleaching. This microorganism possesses redundancy of genes encoding ATP-independent chaperone holdases like Hsp20 (hps20.1, hsp20.2, and hsp20.3), Hsp31, Hsp33, RidA (ridA.1 and ridA.2), and Lon (lon.1, lon.2, and lon.3), and single copy genes encoding SlyD and CnoX. We evaluated the response of these holdases to short and long-term stresses induced by changes in temperature (30° to 37 °C), pH (1.6 to 1.2 or 2.0), and oxidative status (1 mM H2O2) as well as to different energy sources (iron, sulfur, pyrite, sphalerite or chalcopyrite). Cells adapted under thermal and oxidative stress conditions showed a generalized upregulation of holdase genes, while short-term stress led to more discrete increases in transcript levels, with only hsp20.2 and hsp31 showing higher mRNA levels. hsp31 was also upregulated under acidic stresses, sulfur and sulfides. hsp20 variants showed different mRNA levels under different conditions, and cnoX was induced under oxidative conditions. Cells cultured on chalcopyrite had similar responses to those grown with peroxide. With some exceptions, stresses led to significant increases in intracellular ROS content, and decreases in ATP. These results pave the way to understanding proteostasis systems in extreme acidophilic bacteria. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.